Eurasian Integration as a Strategic Choice of Russia - I. A. Vetrenko (Евразийская интеграция: экономика, право, политика)
The article is devoted to the analysis of the current state of Eurasian integration and the significance of the Eurasian ideology in this process. The main goal is to answer the question whether the time has come forEurasiato lead from a geopolitical position. The relevance of the topic is confirmed not only by numerous interdisciplinary studies, but also by real political integration processes. The analysis of the Customs Union's activities is presented as an effective tool for Eurasian integration.